FRI0162 Antibody response to 13-valent pneumococcal conjugate vaccine is not impaired in patients with rheumatoid arthritis (RA) or sjogrens syndrome without dmard treatment compared to controls. (15th June 2017) - Nived, P; Nagel, J; Saxne, T; Geborek, P; Mandl, T; Skattum, L; Kapetanovic, MC
Abstract : Objectives: To investigate if antibody response and functionality of antibodies following immunization with 13-valent pneumococcal conjugate vaccine (PCV13) is impaired in patients with rheumatoid arthritis (RA) and primary Sjogrens syndrome (pSS) without treatment, with methotrexate (MTX) or hydroxychloroquine (HCQ), compared to healthy controls. Methods: In total, 61 patients with RA (51 without DMARD and 10 on MTX), 23 patients with pSS (18 without DMARD and 5 on HCQ) and 49 controls were vaccinated with a single dose (0.5 ml) PCV13 intramuscularly. Pre- and postvaccination serotype-specific antibody concentrations for pneumococcal serotypes 6B and 23F and functionality of antibodies (23F) were determined in serum samples taken immediately before and 4–6 weeks after vaccination using ELISA and opsonophagocytic activity (OPA) assay, respectively. Proportions of individuals with positive antibody response (i.e. ≥2-fold increase from prevaccination concentrations) for both serotypes were calculated and groups were compared using Chi2 test. Percentage change (pre- to postvaccination) in OPA was calculated and groups were compared using Mann-Whitney U test. Results: Pre- to postvaccination antibody concentrations (Table) increased significantly for both serotypes and in both patient and control groups ( p <0.001). Antibody response to serotypes 6B and 23F was decreased in patients with RA on MTX treatment (both p <0.01), but not in RA without DMARD or pSS with or without HCQ, compared to controls (Figure). Proportions of antibody responders to both serotypes did not differ significantly between groups RA without DMARD (51%), pSS (48%) and controls (55%). After vaccination, OPA increased in groups RA without DMARD ( p <0.001), pSS without DMARD ( p =0.01) and controls ( p <0.001), but did not change significantly in patients with RA on MTX and pSS on HCQ. The mean percentage change in OPA was lower in RA on MTX (1.8%, p =0.01), RA without DMARD (8.9%, p <0.01) and pSS on HCQ (-1.5%, p =0.01), but not in pSS without DMARD (11.0%), compared to controls (17.9%). Conclusions: Pneumococcal conjugate vaccine is immunogenic in patients with RA and pSS without DMARD treatment. Both antibody response and functionality of antibodies is impaired in patients with RA on MTX. Disclosure of Interest: None declared